Soluções tipo compacton nos modelos sigmas não-lineares - Lima, Francisco Cleiton Estevão (2019)
In this work, our main purpose is studying compacton-like solutions in the non-linear sigma model, in particular, the sigma-O(3) model with the gauge field governed by the Chern-Simons term. The choice of these models is due to the fact that in both cases, with the minimal coupling, the models present kink-like solutions. In this way, motivated by some recent works of the literature, we seek a generalization of the model to transform the kink-like solutions in compacton-like solutions. In the case of the model with minimal coupling and the gauge field governed by the Chern-Simons term, we observed that the model admits both topological and non-topological solutions for a specific choice of the asymptotic behavior of the gauge field. To finish, we observe that in this case the topological solitons are infinitely degenerate in any sector.